Effect of First‐Line Treatment on Myeloid‐Derived Suppressor Cells' Subpopulations in the Peripheral Blood of Patients with Non–Small Cell Lung Cancer. Issue 8 (August 2016) - Koinis, Filippos; Vetsika, Eleni Kyriaki; Aggouraki, Despoina; Skalidaki, Eleftheria; Koutoulaki, Anna; Gkioulmpasani, Marianthi; Georgoulias, Vassilis; Kotsakis, Athanasios
ABSTRACT : Introduction: : Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of immature cells of myeloid origin whose expression is induced by, among others things, vascular endothelial growth factor. We have previously identified two monocytic and one granulocytic MDSC subpopulations associated with the clinical outcome in patients with non–small cell lung cancer (NSCLC). The aim of the present study was to evaluate the effect of chemotherapy on these MDSC subpopulations. Methods: : Circulating immune cells from 46 patients with unresectable NSCLC were analyzed by flow cytometry before the initiation of chemotherapy and after three cycles. Changes in the frequencies of the MDSC subpopulations were correlated with clinical outcome. Results: : Chemotherapy had no uniform effect on either the number or the functionality of monocytic and granulocytic MDSCs. However, three cycles of bevacizumab‐containing regimens significantly reduced the percentage of the granulocytic‐MDSCs compared with non–bevacizumab‐based regimens ( p = 0.0086). At the time of evaluation of response, disease progression was associated with significantly higher levels of all three MDSC subpopulations compared with in patients with disease control. In patients with disease progression after three cycles of chemotherapy, the percentage of CD15‐positive monocytic MDSCs was significantly increased compared with baseline. Conclusions: : In the peripheral blood of patients with NSCLC, bevacizumab‐based chemotherapy significantly reduced the levels of granulocytic MDSCs. An increase in the levels of CD15‐positive monocytic MDSCs was associated with poor response to treatment and disease progression, providing evidence of their clinical relevance in patients with NSCLC.